A survey on the types of dental implant brands or systems used and the prices charged by implant dentists - Montenegro, Carmencita V.
Dental implants have increasingly become an important treatment option considering the benefits that it can offer to edentulous patients. The awareness of simple facts about this revolutionary dental practice is significant in enhancing restorations of natural teeth. The objective of the study is to know the common brands or systems being used and the prices charged by implant dentists. This study aimed to gather information on the common dental implant brands or systems used that are practical and effective in restoring normal form and function of the missing teeth. The study also aimed to know the prices charged by implant dentists per unit of implant and the factors that affect the cost. Hypotheses testing were done to correlate the data gathered from the interview questionnaires. The results show that the dentists' choice of brands or systems is dependent on the institution where the implant dentists were trained, the length of training, and the age of dentist. The prices charged consequently are dependent on the brands being used. On the other hand, the brands used are not dependent on the type of training and the year of training. Most implant dentists who underwent training abroad, who are in their early 30s, and took formal course use the more popular and high quality brand which is Branemark that is why they charge higher than other implant dentists